What does ‘adaptive programming’ mean in the health sector? - and Tulloch, Olivia (ODI, 2015)
There is considerable interest in the concept of adaptive development and what it may look like in different sectors, including health. Adaptive types of programming from the health sector are relatively advanced; as we work towards the Sustainable Development Goals (SDGs), experiences in health can provide useful lessons for other areas of development. The international health community may not use the label ‘adaptive development’, but many are already conducting adaptive work. ‘Quality improvement’ is one such tried and tested approach. Quality improvement is problem-driven, iterative and flexible. The methodology and principles can be used to identify, test and implement changes in any context or part of a health system. Quality improvement is being used successfully, but there is still limited experience and evidence of how to apply its values and philosophy beyond the project level and embed it within national structures and systems. Systems thinking and analysis of the political economy environment may help embed complex interventions like quality improvement and sustain their achievements